Single-seed sowing increased pod yield at a reduced seeding rate by improving root physiological state of Arachis hypogaea - Xiao-yan LIANG; Feng GUO; Ye FENG; Jia-lei ZHANG; Sha YANG; Jing-jing MENG; Xin-guo LI; Shu-bo WAN (Journal of Integrative Agriculture, 2020)
Double-seed sowing (two seeds per hole) is the dominant pattern of peanut sowing in China, but within-hole plant competition usually limits their growth and yield formation. Besides, the traditional double-seed sowing method does not facilitate mechanization during sowing. The objective of this study was to determine if single-seed sowing at a proper seeding rate yielded better than traditional double-seed sowing pattern and the differences of physiological metabolism of roots. A field experiment was conducted in two consecutive years to compare pod yields of single-seed sowing at 180 000 (S180), 225 000 (S225), and 270 000 seeds ha−1 (S270) with that of double-seed sowing at 270 000 seeds ha−1 (D270) using a completely randomized block design with four replications. And the root bleeding sap rate, nutrient content, and the main hormone contents in root bleeding sap were also comparatively investigated. Although the pod yields of single-seed sowing at the three densities were higher than that of traditional double-seed sowing (D270), S225 yielded better than the other two single-seed sowing treatments (S180 and S270). The increased pod yield in single-seed sowing at 225 000 seeds ha−1 was mainly due to the higher pod dry weight per plant and harvest index. The improved pod dry weight and shoot growth had closely relationship with the enhanced root physiological traits such as the increased root bleeding sap rate, content of free amino acids, soluble sugars, K+, Mg2+, Zn2+, and Ca2+ of the individual plant root. The improved activity of root reductive, nitrate reductase (NR) and ATPase and higher zeatin and zeatin riboside (Z+ZR) content of root bleeding sap were also crucial to the pod and shoot growth of peanut. Single-seed sowing at a moderate seeding rate (S225) is a potential practice to increase pod yield and to save seed cost.